Shock-Induced Turbulent Boundary Layer Separation in Over-Expanded Rocket Nozzles: Physics, Models, Random Side Loads, and the Diffusive Character of Stochastic Rocket Ascent - Keanini, R. G.; Nortey, T. D.; Thorsett-Hill, Karen; Srivastava, N.; Hellman, Sam; Tkacik, P. T.; Knight, P. Douglas (IntechOpen, 2011)
None